Efficient synthesis of O-aryloxime ethers by copper fiuorapatite catalyzed cross-coupling of aryloximes with arylboronic acids - Mulla, Shafeek Abdul Rashid; Chavan, Santosh S.; Inamdar, Suleman M.; Pathari, Mohsinkhan Y.; Shaikh, Taufeekaslam M. Y. (Tetrahedron Letters, 2014)
A novel, highly efficient, and mild protocol has been developed for the synthesis of O-aryloxime ethers in good to excellent yields at ambient reaction conditions. This is the first report in which =N-O-Ar linkage was achieved with ecofriendly, recyclable, heterogeneous copper fluorapatite (CuFAP) catalyst via C-O cross coupling of aryloxime with arylboronic acid in the presence of Cs2CO3 as base and methanol as solvent. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Arylboronic acid; Aryloxime; Copper fluorapatite; O-Aryloxime ethers

Ligand-, base-, co-catalyst-free copper fluorapatite (CuFAP) as a versatile, ecofriendly, heterogeneous and reusable catalyst for an efficient homocoupling of arylboronic acid at ambient reaction conditions - Mulla, Shafeek Abdul Rashid; Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Inamdar, Suleman M.; Shaikh, Taufeekaslam M. Y. (RSC Advances, 2015)
This paper describes the first report in which copper species containing copper fluorapatite (CuFAP) acts as a versatile, eco-friendly, recyclable, heterogeneous catalyst for an efficient synthesis of symmetric biaryls from the homo-coupling of arylboronic acids in methanol solvent at ambient reaction conditions. The developed protocol is ligand-, base-, and co-catalyst-free, sustainable, mild, inexpensive, and compatible with a wide range of aromatic/heterocyclic boronic acids and provides the corresponding products in excellent yields without purification. The catalyst was easily recovered from the reaction mixture and reused several times without loss of activity.

Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles

Base‐promoted heterogeneous reusable copper fluorapatite (CuFAP) catalyzed facile synthesis of 1,2‐diarylethanols via C(sp3)‐H functionalization of nitrotoluene - Shaikh, Taufeekaslam M. Y.; Mulla, Shafeek A. R. (Chemistryselect, 2018)
A novel, an efficient protocol has been developed for the facile synthesis of various 1,2‐diarylethanol in good to excellent yields via C(sp3)‐H functionalization of various nitrotoluenes with substituted aromatic, heterocyclic aldehydes/isatin. This is the first example in which base promoted heterogeneous, reusable copper fluorapatite (CuFAP) catalyzed C(sp3)‐H functionalization of various nitrotoluenes was achieved under ligand‐, additive‐ free reaction condition. The developed protocol is an environmentally benign approach, which replaces cumbersome protocols, avoids the use of costly precious metal catalysts, prefunctionalized substrates, and toxic reagents. The heterogeneous CuFAP catalyst was recovered by simple filtration and reused several times without the loss of its catalytic activity. The selective functional group transformation of 1,2‐diaryethanol was accomplished.

One-pot cascade synthesis of 2-cyanoacrylamides via Sn-catalyzed acetic acid free selective monohydration of dinitrile - Shaikh, Taufeekaslam M. Y.; Mulla, Shafeek A. R. (ChemistrySelect, 2018)
The simple, mild, novel and an efficient new protocol has been developed for the straightforward synthesis of 2-cyanoacrylamides. This is the first report in which Sn-catalyzed acetic acid free selective monohydration of dinitrile was achieved for a one pot cascade synthesis of 2-cyanoacrylamides in good to excellent yield via condensation of various aldehydes, heterocyclic aldehydes with malononitrile.
Keywords: 2-cyanoacrylamides; Aldehyde; one pot; SnCl2 center dot 2H(2)O